2021
DOI: 10.24018/ejmed.2021.3.6.1142
|View full text |Cite
|
Sign up to set email alerts
|

Another Perspective of the Miller Forensic Assessment of Symptoms Test – Part I: A Narrative Review

Abstract: Reference [1] presented a skewed perspective of the M-FAST literature base and provided the flawed conclusion that the M-FAST should no longer be used in practice. In an attempt to correct the many issues with [1], this article provides a narrative review of the strengths and weaknesses of research findings for the M-FAST interpretation as well as reviews methodological concepts underlying feigning research. The M-FAST was designed to screen for potential feigning of psychiatric symptoms. It was not designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…These findings are consistent with those found in other malingering-related meta-analyses (Aparcero et al, 2021; Detullio et al, 2019; Martin et al, 2020). To analyze possible sources of heterogeneity, we selected a set of moderating variables identified in previous research (Aparcero et al, 2021; Detullio, 2021; Detullio et al, 2019; van Impelen et al, 2014). Our findings suggest that the language used may be a moderator variable for the cutoff point FDS ≥ .30, but not for the other two inspected cutoff scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with those found in other malingering-related meta-analyses (Aparcero et al, 2021; Detullio et al, 2019; Martin et al, 2020). To analyze possible sources of heterogeneity, we selected a set of moderating variables identified in previous research (Aparcero et al, 2021; Detullio, 2021; Detullio et al, 2019; van Impelen et al, 2014). Our findings suggest that the language used may be a moderator variable for the cutoff point FDS ≥ .30, but not for the other two inspected cutoff scores.…”
Section: Discussionmentioning
confidence: 99%
“…Because no instrument has yet been developed to assess risk of bias in symptom validity studies, an ad hoc checklist was developed using the methodological flaws identified by Detullio (2021) and Rogers et al (2020). The checklist was composed of 13 items assessing different aspects of the study design that, if absent, constituted a source of bias.…”
Section: Methodsmentioning
confidence: 99%